1979
DOI: 10.1111/j.1365-2621.1979.tb09124.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Evaluation of Textured Sunflower/Soy Protein

Abstract: A blend of sunflower flour/soy flour in the ratio l:l, intended as a meat extender, was extruded in a Wenger X-25 extrusion cooker. The effect of adding textured sunflower/soy flour (TSP) to ground beef was determined by evaluating sensory properties and quality. After preliminary analyses of TSP, sensory tests were performed on a mixture of TSP/beef (30:70), using beef as a control. Panelists detected significant differences at the 1% level for texture and flavor, but could not decide which sample they liked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…No significant differences ( P > 0.05) in juiciness were detected among formulations of ground beef or fresh pork sausage. These findings are similar to those of Vasquez et al. (1979) who found no differences in juiciness between controls and ground beef containing 30% TSP.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…No significant differences ( P > 0.05) in juiciness were detected among formulations of ground beef or fresh pork sausage. These findings are similar to those of Vasquez et al. (1979) who found no differences in juiciness between controls and ground beef containing 30% TSP.…”
Section: Resultssupporting
confidence: 90%
“…No significant differences ( P > 0.05) in juiciness were detected among formulations of ground beef or fresh pork sausage. These findings are similar to those of Vasquez et al (1979) who found no differences in juiciness between controls and ground beef containing 30% TSP. Goltry et al (1976) found that 10% textured soy protein replacement and control sausage were more juicy that those with 20% and 30% TSP replacement.…”
Section: Sensory Characteristics Of Ground Beef and Fresh Pork Sausagesupporting
confidence: 90%
See 3 more Smart Citations